Angular distribution of the soft component of radiation from relativistic electrons near planar orientation in thick single crystals; Russian Physics Journal; Vol. 34, iss. 6 - Amosov K. Yu.; Andreyashkin M. Yu.; Vnukov I. E.; Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sarychev V. P. (1991, 1991)
Title screen